Faktor Internal dan Eksternal terhadap Impulse Buying pada Supermarket Islami - Wenny Pebrianti; Septi Purnama Sari (Cakrawala Management Business Journal, 2022)
This research is conducted to find out the effect of shopping enjoyment tendency, person’s situation, store environment, motivational activities by retailers, and product attributes toward the impulse buying in “Store X” Islamic Supermarket in Singkawang, Kalimantan Barat. The method used in this research is associative, and the technique of data collecting used is questionaire. The population in this research is the all consumers that shop in “Store X” Islamic Supermarket with 100 respondents. The sampling used in this research is non probability sampling accidental sampling and the tool is multiple regression analysis SPSS 21. The result of the data analysis shows that person’s situation, motivational activities by retailers, and product attributes significantly affect the impulse buying, while shopping enjoyment tendency and store environment does not significantly affect the impulse buying.